Regulations on the Determination of Abandoned Land Objects for the Land Bank in the Context of Realizing Agrarian Reform - Ramadhina, Asyifa Aulia Putri; Imam Koeswahyono; Mohammad Hamidi Masykur (CV. AFDIFAL MAJU BERKAH, 2024)
Constitution is the highest basic norm that regulates various aspects of a country's life, including the relationship between state institutions, government, and citizens. In Indonesia, the constitution is known as the 1945 Constitution, which before the amendment only limitedly regulated rights to land and natural resources through Article 33 Paragraph (3). After the amendment, these rights were regulated more firmly, including the recognition of the rights of indigenous peoples and the right to control the state. The regulation of abandoned land is also discussed in the Basic Agrarian Law (UUPA) and PP No. 20 of 2021, which expands the objects of regulation to abandoned land and abandoned areas. Abandoned land can be used as an asset of the Land Bank, an institution formed by the government to manage land optimally. However, the existence of the Land Bank raises concerns regarding legal uncertainty and inequality in land ownership, especially because its broad authority has the potential to ignore the rights of small and indigenous communities. Legal certainty and justice in land distribution must be guaranteed to prevent abuse of power, as well as to fulfill the goals of agrarian reform and community welfare. The method used in this research is a normative legal research method, which is applied to examine regulations related to the Land Bank. This research aims to achieve results that The Land Bank, regulated by PP No. 64 of 2021, aims to manage abandoned land for investment and agrarian reform (TORA), but its implementation risks agrarian inequality, legal uncertainty, and conflicts due to potential dominance by investor interests and deviations in the interpretation of the State's Right to Control (HMN). To achieve equitable, sustainable, and beneficial land use, regulations must be reformed to prioritize justice, transparency, and accountability, ensuring the Land Bank supports small farmers and the public interest in line with Article 33 of the 1945 Constitution and the UUPA.